2017
DOI: 10.3390/rs9040372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Remote Sensing Inversion Error for the Above-Ground Biomass of Alpine Meadow Grassland Based on Multi-Source Satellite Data

Abstract: It is not yet clear whether there is any difference in using remote sensing data of different spatial resolutions and filtering methods to improve the above-ground biomass (AGB) estimation accuracy of alpine meadow grassland. In this study, field measurements of AGB and spectral data at Sangke Town, Gansu Province, China, in three years (2013)(2014)(2015) are combined to construct AGB estimation models of alpine meadow grassland based on these different remotely-sensed NDVI data: MODIS, HJ-1B CCD of China and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The distinction between trees and shrubs is critical for ecosystem assessment in dryland regions because while tree cover in semi-arid regions is an important driver of overall landscape processes and carbon sequestration, seasonal variation in shrub and grass cover is a principal driver of the interannual variability in the carbon cycle [5,46]. Our results thus complement recent studies showing that using high spatial resolution imagery can increase the accuracy of above-ground biomass estimation [47,48].…”
Section: Discussionsupporting
confidence: 73%
“…The distinction between trees and shrubs is critical for ecosystem assessment in dryland regions because while tree cover in semi-arid regions is an important driver of overall landscape processes and carbon sequestration, seasonal variation in shrub and grass cover is a principal driver of the interannual variability in the carbon cycle [5,46]. Our results thus complement recent studies showing that using high spatial resolution imagery can increase the accuracy of above-ground biomass estimation [47,48].…”
Section: Discussionsupporting
confidence: 73%
“…Finally, we found that the RMSE values were small, i.e., 13.35 for the data from Sun [47], 9.40 for Wu et al [48], and 12.15 for their data mixed together ( Figure 2), which indicated that the best-fitted linear model can be applied to AGB peak estimation across the entire study area even though some uncertainties remain. Similar studies that used an empirical model between remote sensing vegetation index and field measured biomass at the local scale to broader spatial scales can also be found on the Tibetan Plateau and other grassland regions of the world [52][53][54][55][56]. Validation of the best-fitted linear AGB peak -GEVI model by comparing the observed AGB peak from (a) Sun [47], (b) Wu, et al [48], and (c) both of them (see Figure 1 for site locations) with the simulated AGB peak values.…”
Section: Agb Peak Estimation At the Regional Scalementioning
confidence: 73%
“…The model was inspected to confirm normality of residuals and homoscedasticity using the Breusch and Pagan test [58]. Since the data for model calibration was limited in size, the GAM model was validated using a leave-one-out cross-validation (LOOCV) method as it has been assessed by earlier work to be appropriate under such constraints [59,60]. The performance of the GAM model was evaluated using adjusted R 2 , deviance and RMSE.…”
Section: Discussionmentioning
confidence: 99%